Application Of Coconut Waste As Green Roof Materials For The Reduction Of Urban Heat Island (UHI) - Nur Ashfahani, Mohamad Sa’edin (2023)
Urbanization's environmental repercussions are mostly due to pollution, atmospheric changes, and soil cover. These effects create the Urban Heat Island (UHI). UHIs contribute to the greenhouse effect, which causes global warming. Due to urbanization and industrialization, UHI is a huge hazard for humans in the 21st century. An Urban Heat Island is a densely populated city or area that is substantially warmer than the surrounding region. The higher temperatures are mainly a result of urban infrastructure and human activity. Rapid and unplanned urbanization affects thermal environment quality in temperate countries, but research in the low tropics, especially quantitative ones, is scarce. A great technology strategy must be introduced to reduce the impact of Urban Heat Island. One of the methods to solve these problems is the application of a green roof system on buildings. The main objective of this study is to construct an extensive green roof system that can reduce the impact of Urban Heat Island using coconut waste as green roof materials as well as to evaluate the performance of green roof in reducing the temperatures of the roof surface and the surrounding air. The design of green roof is based on green roof guidelines. It consists of vegetative layer, substrate layer, filter layer, drainage layer and waterproofing layer. There are three types of prototype model that were evaluated based on thermal reduction which are conventional roof as a control model, commercial green roof and recycled waste green roof. The main focus on recycled green roof is the replacement of commercial material for filter layer and drainage layer which is replaced with coconut fiber and coconut drainage respectively. The outcome of this study has shown that the recycled waste green roof shows the best performance in terms of temperature reduction compared to commercial roof where the temperature decrease from 33°C to 30.5°C. This shows that recycled materials have given a significant impact on the performance of thermal reduction as well as reducing the effect of Urban Heat Island and leading to achieving a sustainable city and communities.